2021
DOI: 10.1177/01455613211016896
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repetitive Transcranial Magnetic Stimulation (rTMS) for Tinnitus: A Retrospective Study

Abstract: Objective: Current studies still find insufficient evidence to support the routine use of repetitive transcranial magnetic stimulation (rTMS) in tinnitus. This study aimed to assess response of tinnitus to treatment with rTMS and identify factors influencing the overall response. Methods: Between January 2016 and May 2017, 199 tinnitus patients were identified from a retrospective review of the electronic patient record at the Sun Yat-sen Memorial Hospital. All patients received rTMS treatment. Their clinicode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…All four of the studies in Table 1 utilized 1 Hz of frequency for a treatment length of 10 days; however, the total amount of pulses per session varied between 1000 and 2000, with varying results in their respective questionnaires used to evaluate patients posttreatment [13,34,41,42]. Wang et al [41], the largest experimental study in this group, found that rTMS was successful in nearly half of the patients when treated with 1 Hz directed over the left temporoparietal cortex for 10 days, as evident by a statistically significant improvement in the VAS-L scores in participants used to characterize tinnitus loudness in participants.…”
Section: Protocols For Rtms and Tinnitusmentioning
confidence: 99%
See 4 more Smart Citations
“…All four of the studies in Table 1 utilized 1 Hz of frequency for a treatment length of 10 days; however, the total amount of pulses per session varied between 1000 and 2000, with varying results in their respective questionnaires used to evaluate patients posttreatment [13,34,41,42]. Wang et al [41], the largest experimental study in this group, found that rTMS was successful in nearly half of the patients when treated with 1 Hz directed over the left temporoparietal cortex for 10 days, as evident by a statistically significant improvement in the VAS-L scores in participants used to characterize tinnitus loudness in participants.…”
Section: Protocols For Rtms and Tinnitusmentioning
confidence: 99%
“…Negative predictors of treatment success were identified, such as the length of symptoms, presence of hearing loss, and presence of sleep disturbance [41]. In a retrospective study of 199 patients, Yang et al [13] noted significant results in a total of 62.3% of patients following treatment with 2000 pulses at 1 Hz. They noted the most pronounced improvement, of 82.8%, in the group that only had symptoms for 1 week, compared to 67.2% of patients who had symptoms longer than a year [13].…”
Section: Protocols For Rtms and Tinnitusmentioning
confidence: 99%
See 3 more Smart Citations